Effects of a single subanaesthetic dose of ketamine on pain and mood after laparoscopic bariatric surgery: A randomised double-blind placebo controlled study. Issue 1 (January 2019) - Wang, Jing; Echevarria, Ghislaine C.; Doan, Lisa; Ekasumara, Nydia; Calvino, Steven; Chae, Floria; Martinez, Erik; Robinson, Eric; Cuff, Germaine; Franco, Lola; Muntyan, Igor; Kurian, Marina; et al.
Abstract : BACKGROUND: When administered as a continuous infusion, ketamine is known to be a potent analgesic and general anaesthetic. Recent studies suggest that a single low-dose administration of ketamine can provide a long-lasting effect on mood, but its effects when given in the postoperative period have not been studied. OBJECTIVE: We hypothesised that a single low-dose administration of ketamine after bariatric surgery can improve pain and mood scores in the immediate postoperative period. DESIGN: We performed a randomised, double-blind, placebo-controlled study to compare a single subanaesthetic dose of ketamine (0.4 mg kg −1 ) with a normal saline placebo in the postanaesthesia care unit after laparoscopic gastric bypass and gastrectomy. SETTING: Single-centre, tertiary care hospital, October 2014 to January 2018. PATIENTS: A total of 100 patients were randomised into the ketamine and saline groups. INTERVENTION: Patients in the ketamine group received a single dose of ketamine infusion (0.4 mg kg −1 ) in the postanaesthesia care unit. Patients in the placebo groups received 0.9% saline. OUTCOME MEASURES: The primary outcome was the visual analogue pain score. A secondary outcome was performance on the short-form McGill's Pain Questionnaire (SF-MPQ). RESULTS: There were no significant differences in visual analogue pain scores between groups (group-by-time interaction P  = 0.966; marginal group effect P  = 0.137). However, scores on the affective scale of SF-MPQ (secondary outcome) significantly decreased in the ketamine group as early as postoperative day (POD) 2 [mean difference = −2.2 (95% bootstrap CI −2.9 to 1.6), Bonferroni adjusted P  < 0.001], compared with placebo group in which the scores decreased only by POD 7. Scores on the total scale of SF-MPQ for the ketamine group were smaller compared with the placebo group ( P  = 0.034). CONCLUSION: Although there was no significant difference between ketamine and placebo for the primary outcome measure, patients who received ketamine experienced statistically and clinically significant improvement in their comprehensive evaluation of pain, particularly the affective component of pain, on POD 2. However, future studies are needed to confirm the enduring effects of ketamine on the affective response to postoperative pain. CLINICAL TRIAL REGISTRATION: NCT02452060. N/A: This article is accompanied by the following Invited Commentaries: Mion G. Ketamine stakes in 2018. Right doses, good choices. Eur J Anaesthesiol 2019;36 :1–3. Robu B, Lavand'homme, P. Targeting the affective component of pain with ketamine. A tool to improve the postoperative experience? Eur J Anaesthesiol 2019;36 :4–5.